1999
DOI: 10.1095/biolreprod61.6.1409
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Recombinant Ovine Interferon Tau, Placental Lactogen, and Growth Hormone on the Ovine Uterus1

Abstract: Studies were conducted to determine effects of intrauterine administration of recombinant ovine interferon tau (IFNtau), placental lactogen (PL), and growth hormone (GH) on endometrial function. In the first study, administration of IFNtau to cyclic ewes for one period (Days 11-15) resulted in an interestrous interval (IEI) of approximately 30 days, whereas administration for two periods (Days 11-15 and Days 21-25) extended the IEI to greater than 50 days. Administration of IFNtau from Days 11 to 15 and of PL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
125
2
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(136 citation statements)
references
References 70 publications
8
125
2
1
Order By: Relevance
“…Another conceptus-related signal may be responsible for the difference in expression of UTMP in the uteri of large pregnancies. One such candidate is CSH1, as it has been reported to stimulate the number of glands present in ovine endometrium and, hence, the levels of UTMP and SPP1 mRNA present (Spencer et al 1999).…”
Section: Evaluation Of the Bovine Uterine Environmentmentioning
confidence: 99%
“…Another conceptus-related signal may be responsible for the difference in expression of UTMP in the uteri of large pregnancies. One such candidate is CSH1, as it has been reported to stimulate the number of glands present in ovine endometrium and, hence, the levels of UTMP and SPP1 mRNA present (Spencer et al 1999).…”
Section: Evaluation Of the Bovine Uterine Environmentmentioning
confidence: 99%
“…GH is expressed in the sheep placenta mainly during the early stages of pregnancy and it is involved in regulating endometrial gland proliferation and function (Spencer et al, 1999). Interestingly, Valinsky et al (1990), showing the occurrence of gene duplication in the ovine GH locus, found two alleles: the GH1 allele with a single GH copy, and the GH2 allele with two gene copies designated GH2-N and GH2-Z.…”
Section: Function Of the Hypothalamic-pituitary-adrenal (Hpa) Axismentioning
confidence: 99%
“…Early studies of endocrine regulation of expression of proteins secreted by uteri of pigs (uteroferrin, ACP5; Knight et al 1973) and sheep (serine protease inhibitors or uterine milk proteins; Moffat et al 1987) revealed a requirement for longterm treatment with P 4 , indicating that effects of P 4 were not mediated by a 'classical' steroid receptor-type mechanism of action. Based on current evidence, longterm treatment with P 4 is required in order to downregulate PGR as a prerequisite to expression of proteins such as uteroferrin and uterine milk proteins in response to one or more progestamedins (Spencer et al 1999, Spencer & Bazer 2002. P 4 , the hormone of pregnancy, is required for establishment and maintenance of pregnancy in all mammals (see Bazer et al 2009).…”
Section: Introductionmentioning
confidence: 99%